2011
DOI: 10.2105/ajph.2010.300061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Health Care System Distrust on Breast and Cervical Cancer Screening in Philadelphia, Pennsylvania

Abstract: Objectives This study investigates whether health care system distrust is a barrier to breast and cervical cancer screening and whether different dimensions of distrust – values and competence – have different impacts on cancer screening. Methods We utilize data on 5,268 women 18 and older living in Philadelphia and analyze their use of screening services via logistic and multinomial logistic regression. Results High levels of health care system distrust are associated with lower utilization of breast and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 38 publications
3
77
1
Order By: Relevance
“…At the individual level, obstacles to care identified have included low education level, 10 poor health literacy, 11 concerns about test efficacy, 12 and language and cultural beliefs related to cancer, distrust, and fear. [13][14][15] Compounded with these concerns, systems barriers such as difficulty accessing highquality diagnostic services, 16 variability in site of care, 17 poor access to primary care physicians or specialists, 18 and lack of insurance, 19,20 can impact adherence to cancer-related care. Health care reform provisions target financial barriers to access to cancer care but will unlikely attenuate the full range of obstacles to care.…”
Section: Introductionmentioning
confidence: 99%
“…At the individual level, obstacles to care identified have included low education level, 10 poor health literacy, 11 concerns about test efficacy, 12 and language and cultural beliefs related to cancer, distrust, and fear. [13][14][15] Compounded with these concerns, systems barriers such as difficulty accessing highquality diagnostic services, 16 variability in site of care, 17 poor access to primary care physicians or specialists, 18 and lack of insurance, 19,20 can impact adherence to cancer-related care. Health care reform provisions target financial barriers to access to cancer care but will unlikely attenuate the full range of obstacles to care.…”
Section: Introductionmentioning
confidence: 99%
“…(6-8) Some organizational features have been shown to have a major impact on rates of breast, cervical, and colorectal cancer screening. (9-11) Stone et al (9), for example, identified three general clinic-based strategies that increased screening delivery: use of separate clinics devoted to prevention, use of a planned care visit for prevention, and designation of non-physician staff to do specific prevention activities.…”
Section: Introductionmentioning
confidence: 99%
“…One study found that a positive smoking status served as a barrier in an individual’s medical help–seeking behavior (Stuber, Galea, & Link, 2008), and another reported that individuals frequently delayed seeking medical help because they expected blame for their illness regardless of their smoking status (Tod et al, 2008). Healthcare system distrust has been identified as a barrier to timely breast and cervical cancer screening and may influence medical help–seeking behavior in people with lung cancer symptoms (Katapodi, Pierce, & Facione, 2010; Yang, Matthews, & Hillemeier, 2011). Healthcare system distrust was related to delayed medical help–seeking behavior in symptoms of breast cancer and subsequent advanced breast cancer stage at diagnosis (Friedman et al, 2006; Gould, Fitzgerald, Fergus, Clemons, & Baig, 2010; Taib, Yip, & Low, 2011).…”
mentioning
confidence: 99%